DETERMINATION OF VITAMIN C CONTENT IN BELL PEPPER (Capsicum annuum L.) WITH DIFFERENT PROTIC POLAR SOLVENT BY UV-VIS SPECTROSCOPY - Afnani, Fawait; Yanti, Jamilah Hamidi; Pratiwi, Wiwit Sri Werdi (Universitas Airlangga, Campus C Mulyorejo, Surabaya, Indonesia, 2023)
Bell pepper can be an antioxidant and has many health benefits because of the high content of vitamin C. Vitamin C contents in yellow and orange bell peppers were extracted using different protic polar solvents and analyzed using the UV-Vis Spectrophotometry method. In this research, the bell peppers were extracted using the maceration technique for two days in 90% concentration of solvents (methanol and ethanol, respectively). Subsequently, the maximum wavelength was determined, and then 100 ppm ascorbic acid was used as a standard solution to analyze vitamin C content. Linearity based on a calibration curve is used to obtain the correlation coefficient of concentration between the standard solution and vitamin C levels in the sample. The result of UV-Vis spectroscopy analysis of this sample shows 373.5 nm of Î»max. The linearity is shown in the equation y = 0.0006 x + 0.019. The vitamin C content in all samples had significant differences based on randomized complete block design (RCBD) test result with α = 0.05. The vitamin C level in the yellow pepper sample with an ethanol solvent (340 mg/100 g) was higher than that of the orange pepper sample with ethanol (251 mg/100 g). Meanwhile, the vitamin C content in the sample of yellow peppers with methanol solvent (562.5 mg/100 g) was smaller than that of orange peppers with methanol solvent (757.5 mg/100 g). These contents indicated a different result in the level sources of vitamin C, even if the maceration process used a solvent with a higher dielectric constant.